The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1097/pas.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Gleason Pattern 5 Prostate Adenocarcinoma on Core Needle Biopsy

Abstract: Accurate recognition of Gleason pattern 5 (GP5) prostate adenocarcinoma on needle biopsy is critical as it is associated with disease progression and adverse clinical outcome. Despite important implications of this diagnosis, interobserver variation in the diagnosis of GP5 has not been adequately studied. Digital images of 66 prostate adenocarcinoma cases that potentially contained a GP5 component were distributed to 16 urologic pathologists who were asked to classify whether GP5 was present. Each image was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Substantial additional variability arises from applying discrete categorizations to glandular differentiation that lies on a continuous spectrum, such as the Gleason pattern 3/4 transition between small glands and poorly defined acinar structures or the Gleason pattern 4/5 transition between fused glands and nests or cords. 12,44,45 Our data show that for regions where pathologists are discordant in Gleason pattern categorization, where the underlying histology is likely closer to the cusp between patterns, the DLS reflects this ambiguity in its prediction scores (Fig. 4b) and demonstrates the potential to assign finer-grained Gleason patterns (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Substantial additional variability arises from applying discrete categorizations to glandular differentiation that lies on a continuous spectrum, such as the Gleason pattern 3/4 transition between small glands and poorly defined acinar structures or the Gleason pattern 4/5 transition between fused glands and nests or cords. 12,44,45 Our data show that for regions where pathologists are discordant in Gleason pattern categorization, where the underlying histology is likely closer to the cusp between patterns, the DLS reflects this ambiguity in its prediction scores (Fig. 4b) and demonstrates the potential to assign finer-grained Gleason patterns (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Based on the above-mentioned mutual relation of growth patterns, we hypothesize that small solid nests might be precursor lesions of fused glands prior to lumen-formation. Interestingly, Shah et al found overall consensus among 16 urologic pathologists for calling large (>20 cells) solid fields Gleason pattern 5, but not for medium (10-20 cells) or small (<10 cells) solid nests, further questioning the precise clinicopathologic relevance of smaller sized solid fields [46].…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional continuity of these patterns is reflected by the substantial inter-observer variability in daily pathology practice. Distinguishing, on one hand, tangentially sectioned Gleason pattern 3 glands from poorly formed and fused Gleason pattern 4 glands, and, on the other hand, poorly formed Gleason pattern 4 glands from Gleason pattern 5 cords on hematoxylin and eosin slides is the principal area of difficulty [12, 14, 27, 28]. Secondly, there are serpentine compact irregular epithelial proliferations, consisting of cribriform Gleason pattern 4 and solid Gleason pattern 5, with decreasing inter-epithelial lumen sizes and frequencies.…”
Section: Discussionmentioning
confidence: 99%